The Personalized System of Instruction: Review and Applications to Distance Education - Grant, Lyle K.; Spencer, Robert E. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
The present paper (a) outlines the basic features of the Personalized System of Instruction (PSI); (b) provides a brief history of PSI; and (c) describes the application of PSI to distance education. Some common misconceptions about PSI are also addressed. PSI is presented as a helpful universally applicable set of instructional practices that are well suited to distance teaching and learning.